Caracterização química e mineralógica da incrustação em rede de ferro fundido e potencial de recuperação da capacidade hidráulica - Moruzzi, Rodrigo Braga [UNESP]; Conceicao, Fabiano Tomazini da [UNESP]; Beltran Navarro, Guillermo Rafael [UNESP]; Zanardo, Antenor [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2012)
The purpose of this work was to characterize chemical and mineralogical the water supply networks and to assess the hydraulic recovery on high-degraded pipe. Thus, the resistance (by pitometric essays), chemical analyses (ICP-MS and ICP-ES), mineralogical analysis (petrographic thin sections, X-ray difractometry and scanning electronic microscopy), hardness (Mohs scale) and simulations for pipe's change and rehabilitations scenarios were investigated (from Scenario 1 to 4). The results showed that the high-degraded pipe had a limited recovery (from 3,9 to 14,0 m(0,367).s(-1)). The deposits were formed by oxide and hydroxide of iron (magnetite and goethite), which are materials of high hardness (6 on Mohs scale). The simulations indicated the required power ratio (C-i/C-1) around 86.00, 1.00 and 0.02% in relation to present scenario.
Chemical and mineralogical incrustation characterization and potential of hydraulic performance recovery
Keywords: water supply network; deposits; inlay; head-loss